Suitability of measurements used to assess mental health outcomes in men and women trafficked for sexual and labour exploitation: a systematic review. (May 2016) - Doherty, S; Oram, S; Siriwardhana, C; Abas, M
Summary: Trafficking is a global human rights violation with multiple and complex mental health consequences. Valid and reliable mental health assessment tools are needed to inform health-care provision. We reviewed mental health assessment tools used in research with men and women trafficked for sexual and labour exploitation. We searched nine electronic databases (PsycINFO, Ovid Medline, PubMed, Embase, Assia, the Web of Science, Global Health, Google Scholar, and Open Grey) and hand-searched the reference lists of relevant identified studies. Seven studies were included in this Review. Six of the studies screened for post-traumatic stress disorder, depression, and anxiety; one study screened for harmful use or abuse of alcohol and used a diagnostic tool to assess post-traumatic stress disorder, depression, and anxiety. Two studies included men in their sample population. Although the reported prevalence of mental health problems was high, little information was provided about the validity, reliability, and cultural appropriateness of assessment tools. Further research is needed to determine which assessment tools are culturally appropriate, valid, and reliable for trafficked people.